2008
DOI: 10.1088/0967-3334/30/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Electrode configurations for detection of intraventricular haemorrhage in the premature neonate

Abstract: Intraventricular haemorrhage is a common cause of death in premature human infants. As preventative measures and treatments become available, a method for monitoring and detection is required. Electrical impedance tomography (EIT) is a viable monitoring method compared to modalities such as ultrasound, MRI or CT because of its low cost and contrast sensitivity to blood. However, its sensitivity to blood may be obscured by the low conductivity skull, high conductivity cerebrospinal fluid (CSF) and shape changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…In previous papers (Sadleir and Tang 2009, Sadleir et al 2009, Tang et al 2010, Tang and Sadleir 2010, 2011) we described promising results in numerical simulations and phantom experiments. We found that an 16-electrode layout based on the electroencephalograph (EEG) 10–20 layout, combined with a measurement strategy that involved applying a sequence of current patterns with all return paths over the anterior fontanel (the ‘Cz pattern’) was superior to other patterns considered.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…In previous papers (Sadleir and Tang 2009, Sadleir et al 2009, Tang et al 2010, Tang and Sadleir 2010, 2011) we described promising results in numerical simulations and phantom experiments. We found that an 16-electrode layout based on the electroencephalograph (EEG) 10–20 layout, combined with a measurement strategy that involved applying a sequence of current patterns with all return paths over the anterior fontanel (the ‘Cz pattern’) was superior to other patterns considered.…”
Section: Introductionmentioning
confidence: 83%
“…The sensitivity matrix may be computed from a finite element model of the imaged domain (Sadleir and Tang 2009). We found that reliable representations of introduced anomalies were produced when the head was modeled as a homogeneous sphere (Tang and Sadleir 2011), and this model was used as the sensitivity matrix in the in vivo reconstructions presented here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EIT systems have been reported to be used as research devices to investigate lung function, brain function, heart function, breast cancer, etc. 4,5,9,11,13,18,20 The region of interest within the cross-sectional images is well defined and EIT has the potential for quantification and visualization of regional ventilation. 1,10 In the case of abdominal applications, gastric function has been studied and assessed using EIT.…”
Section: Introductionmentioning
confidence: 99%